Loading....
Coupon Accepted Successfully!

 

Parentheses

When simplifying expressions with nested parentheses, work from the inner most parentheses out:
5x + (y – (2x – 3x))
= 5
x + (y – (–x))
= 5
x + (y + x) = 6x + y
 
Sometimes when an expression involves several pairs of parentheses, one or more pairs are written as brackets. This makes the expression easier to read:
 

2x(x – [y + 2(xy)]) =
2x(x – [y + 2x – 2y]) =
2x(x – [2xy]) =
2x(x – 2x + y) =
2x(–x + y) =
–2x2 + 2xy





Test Your Skills Now!
Take a Quiz now
Reviewer Name